McPhail Dressage Chair of Equine Sports Medicine
We are currently designing a new Equine Performance Center that will integrate our clinical and research studies of performance horses and lameness. It will be the Midwest's leading veterinary diagnostic and treatment facility for performance horses. The proposed building will be a state-of-the-art facility for clinical and research studies of equine performance problems in all types of horses. In addition to housing our gait analysis equipment it will contain an indoor arena for lunging, riding and driving and firm surfaces for lunging and evaluating horses on a straight line The MSU Equine Hospital is already equipped with a wide range of diagnostic techniques including radiology, ultrasound, scintigraphy, CT scanning, endoscopy, and arthroscopy. The specialized services provided by the new Equine Performance Center will further expand our clinical and research capabilities by exploiting the potential diagnostic value of gait analysis. The projected cost of the Equine Performance Center is $1.3 m , and a fund-raising campaign is underway both for the building and for establishing a $2 m Equine Performance Program Endowment to ensure the continued strength of the College of Veterinary Medicine at MSU as a center of excellence for equine research and education. The endowment is being established as a result of our strong commitment to equine research at MSU. At this time we feel it is important to have dedicated funds available to ensure the continuance of these research efforts in the face of budget cuts within the university and uncertainty about external funding sources. The Equine Performance Program Endowment will provide secure funding for future research. In addition to our clinical and research activities, the College of Veterinary Medicine is responsible for educating the next generation of equine veterinarians, and it is important to maintain a high standard in both our DVM and graduate programs. These programs will benefit greatly from both the research endowment and the new Equine Performance Center. These initiatives will also enhance our ability to offer continuing education programs for veterinarians, and to offer veterinary-related educational courses for horse people.